Social behaviour and circadian variations in different activities of captive hog deer (Axis porcinus) - Farooq, Zahid; Baboo, Irfan; Younas, Muhammad; Iqbal, Khalid Javed; Asad, Sana; Shahbaz, Muhammad; Munir, Muhammad Mazhar; Saleem Khan, Muhammad; Wajid, Muhammad (Penerbit Universiti Kebangsaan Malaysia, 2021)
Management practices/strategies to re-modulate the wild behaviour of animal species could increase their number in natural areas. The captive herd of hog deer showed slight changes from wild behaviour due to captive stress with no alteration in wild behaviour pattern except captive stress. Adult males (6), adult females (6) and fawns (6) were selected and observed round the clock for thirty days across season after one-hour interval on each activity. All subjects in hotter part of the day spent more time in sitting and rest. While, few hours of night in sleeping, resting and rumination. Fawn spent more time in sitting, resting, and hiding compared to adults. During wandering, they also spent some time in standing. It was noticed that all hog deer in herd not slept together but few of them remain active. Only male fighting was observed and maximum was noticed in August and September during breeding season. Hog deer were mainly crepuscular in feeding with irregular short intakes, and grazing on grasses present in enclosure. This study provides guideline to rehabilitate wild hog deer for better breeding management, conservation and raising practices.